1999
DOI: 10.1159/000054496
|View full text |Cite
|
Sign up to set email alerts
|

The Insulin-Like Growth Factor System in the GT1-7 GnRH Neuronal Cell Line

Abstract: Evidence suggests that insulin-like growth factors (IGFs; IGF-I and IGF-II) are involved in the regulation of reproductive function including the development of the gonadotropin-releasing hormone (GnRH) neuronal system and the modulation of GnRH secretory activities. To further characterize the regulatory role of the IGF system on GnRH neuronal function, we have examined the gene expression of IGF-I, IGF-II, IGF-I receptor (IGF-IR), and IGF-binding proteins (IGFBPs) in a GnRH neuronal cell line (GT1-7 cells). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 33 publications
3
22
0
3
Order By: Relevance
“…In vitro stimulation of GnRH neurons with insulin increases GnRH expression and release (11,(14)(15)(16). IGF-1 stimulation also increases GnRH expression (17,18) and release (19) in vitro. We sought to determine whether direct action of insulin and IGF-1 on the GnRH neuron plays a role in regulation of puberty and reproduction in vivo.…”
Section: Introductionmentioning
confidence: 94%
“…In vitro stimulation of GnRH neurons with insulin increases GnRH expression and release (11,(14)(15)(16). IGF-1 stimulation also increases GnRH expression (17,18) and release (19) in vitro. We sought to determine whether direct action of insulin and IGF-1 on the GnRH neuron plays a role in regulation of puberty and reproduction in vivo.…”
Section: Introductionmentioning
confidence: 94%
“…Previous reports found that insulin did not increase GnRH release from the GT1-7 cell line, a GnRH secreting immortalized cell line, after two hours of insulin exposure in static culture (Olson et al, 1995;Anderson et al, 1999). At supraphysiologic concentrations, insulin has been shown to affect GnRH secretion in a model of conditionally immortalized and GnRH expressing rat hypothalamic neurons in perifusion experiments (Salvi et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…These data suggest a mediatory role for PGE2 in TGF-α-stimulated GnRH secretion by GT1–7 cells. In contrast, IGF-I acts directly on GT1–7 cells, which also express IGF-I receptor [32]. Treatment of GT1–7 cells with IGF-I or IGF-II stimulated GnRH secretion by GT1–7 cells during the first 2 h of treatment [32].…”
Section: Discussionmentioning
confidence: 99%
“…GT1–7 cells were first grown at 37°C in a humidified atmosphere of 95% air and 5% CO 2 in 10% fetal bovine serum (FCS)-supplemented Dulbecco’s modified Eagle medium (DME), then cultured in serum-free medium containing glucose and penicillin/streptomycin as previously described by Anderson et al [32]. After 24 h in serum-free medium, GT1–7 cells were cultured for an additional 12 h in 100% astrocyte-conditioned media or control serum-free F12/DME media.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation